Student Life Transformed: A Post-World War Two Institutional Case Study of St. Francis Xavier University - Cameron, James D. (Canadian Journal of Higher Education, 2003)
This paper is an institutional case study of how post-World War II social trends reconfigured Canadian universities and colleges and thus substantially altered the undergraduate experience. The study focuses on the church-related college of St. Francis Xavier University in Antigonish, Nova Scotia. By marshalling a combination of salient documentary, oral, survey, and statistical evidence, the author concludes that critical processes, such as rising enrolments, physical plant expansion, faculty laicization, the campaign for student power, and gradual integration of the sexes transformed key dimensions of student life. Pronounced changes occurred in the sociology of residence life, in student attitudes to institutional authority, in student-faculty relations, in institutional decision-making processes, in gender relations, in program offerings and curricular regulations, in rules governing student social life, and in the role of religion. Consequently, the student who enrolled after the 1960s entered a markedly different institution than the student's predecessor who had been admitted as an undergraduate before 1945. The research demonstrates the value of the close analysis of student life at the local institutional level in the post-war era for understanding the contours of the contemporary undergraduate experience.